A study to Establish a Protocol for Cultivation of Jatropha curcas Linn - Rahman, MM; Banu, LB; Uddin, MN; Begum, MM (Bangladesh Journal of Scientific and Industrial Research, 2010)
Survival rate of stem cutting, vegetative and reproductive growth studies were performed with Jatropha curcas. Plant species were collected from different topographical regions of Bangladesh viz. Chittagong, Sylhet, Jessore and Thakurgaon. No organic, inorganic fertilizer or plant hormone were used in this experiment. Results of the study revealed that best performance in respect of vegetative growth and reproductive growth was found in field condition. The study also showed that survival rate of stem cutting is highest in pot. The maximum survival rate (42.7%) for stem cutting was found during the month of March. Stem cutting collected from Chittagong showed best performance. The results suggested that genome collection and cultivation of Jatropha curcas performed best in summer season, specifically from March to early April, which is unusual to other plants in our country. It also suggested that to cultivate J. curcas in level land like Dhaka, steam cutting should be collected from hilly areas of Bangladesh like Chittagong district for more survival rate of plants. Key words: Jatropha curcas; growing season; fertilizer; soil pH; survival percentage. DOI: 10.3329/bjsir.v44i4.4598 Bangladesh J. Sci. Ind. Res. 44(4), 457-460, 2009